Spatial-temporal analysis of urban environmental quality of Tehran, Iran - Mohammad Javanbakht (Elsevier, 2021)
Urban environmental quality (UEQ) is a quantifiable measure of the capacity of an environment to cope with the requirements of an urban population. UEQ can be mapped by way of modeling separate domains of a specific residential area, such as physical environment, buildup areas, infrastructure, natural hazards, etc. Along this thread, the present study sets out to design a unprecedented approach to spatial-temporal mapping of UEQ based on Fuzzy logic, analytical network process, remote sensing imagery, and field‐collected data. The methods were implemented for the case of districts 3, 6, and 11 of Tehran. As maintained by the results of sensitivity analysis, the introduction of a 30 percent error to the input parameters, resulted in a mere 16 percent change in output, signifying high reliability of the developed spatial temporal modeling proposed in this study as a reasonably suitable model for environmental quality mapping in heterogeneous urban areas. The following conclusions were made based on the study findings: (i) the spatial pattern of UEQ follows along a north-south trend, (ii) UEQ is higher in spring and summer compared to winter and autumn, (iii) air quality index and vegetation cover are the most influential indicators for UEQ mapping and modeling.